Astrocytes in Neuropathologies Affecting the Frontal Cortex - Peteri, Ulla-Kaisa; Niukkanen, Mikael; Castrén, Maija L. (Frontiers in Cellular Neuroscience, 2019)
To an increasing extent, astrocytes are connected with various neuropathologies. Astrocytes comprise of a heterogeneous population of cells with region- and species-specific properties. Frontal cortex exhibits high level of plasticity required for high cognitive functions and memory making this region especially susceptible to damage. Aberrations in the frontal cortex are involved with several cognitive disorders, including Alzheimer’s disease, Huntington’s disease and frontotemporal dementia. Human induced pluripotent stem cells (iPSCs) provide an alternative for disease modeling and offer possibilities for studies investigating pathological mechanisms in a cell type-specific manner. Patient-specific iPSC-derived astrocytes have been shown to recapitulate several disease phenotypes. Addressing astrocyte heterogeneity may provide improved understanding of the mechanisms underlying neurodegenerative diseases.